2022
DOI: 10.1097/sih.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Training in Disaster Medicine

Abstract: Statement: Disaster medicine (DM) training aims to recreate stressful, mass casualty scenarios faced by medical professionals in the field with high fidelity. Virtual (VR) and augmented reality (AR) are well suited to disaster training as it can provide a safe, socially distant simulation with a high degree of realism. The purpose of this literature review was to summarize the current use of VR or AR for simulation training of healthcare providers in DM education. A systematic review of peer-reviewed articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
4
7
0
Order By: Relevance
“…This umbrella review examined the literature to elucidate the use of metaverse in nursing education. In accordance with similar reviews,11,42,43 findings demonstrated that the metaverse engages students to learn multifaceted content. Metaverse research received attention during the COVID-19 pandemic42–44; yet, 7 of the included reviews were conducted before the pandemic.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This umbrella review examined the literature to elucidate the use of metaverse in nursing education. In accordance with similar reviews,11,42,43 findings demonstrated that the metaverse engages students to learn multifaceted content. Metaverse research received attention during the COVID-19 pandemic42–44; yet, 7 of the included reviews were conducted before the pandemic.…”
Section: Discussionsupporting
confidence: 84%
“…In accordance with similar reviews,11,42,43 findings demonstrated that the metaverse engages students to learn multifaceted content. Metaverse research received attention during the COVID-19 pandemic42–44; yet, 7 of the included reviews were conducted before the pandemic. Although most reviews recognized metaverse as a promising pedagogical tool, several reviews31,34,35,39 reported mixed results in certain outcomes between metaverse education and traditional approaches, a not uncommon finding as similar studies comparing metaverse interventions with traditional methods reported mixed effectiveness 9,45–47…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…2 On an individual level, simulation can be utilised to assess technical and non-technical skills, improve knowledge and performance, and elucidate human factors at play during an emergency. 3,21 Collaboration between agencies is a critical component of disaster response, and simulation incorporating agencies external to the ED will improve knowledge and understanding of disaster response for trainees. 23 However, disasters never follow a logical, predetermined path, and although simulation will support skill development, nothing can prepare for a disaster than a disaster.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation is known to improve interpersonal communication, and to increase clinician confidence to respond to situations within a multi‐disciplinary environment 2 . On an individual level, simulation can be utilised to assess technical and non‐technical skills, improve knowledge and performance, and elucidate human factors at play during an emergency 3,21 . Collaboration between agencies is a critical component of disaster response, and simulation incorporating agencies external to the ED will improve knowledge and understanding of disaster response for trainees 23 .…”
Section: Discussionmentioning
confidence: 99%